Choreographed Rhythms – Thoughts and Practical Suggestions on Music and Movement - Rodrigues, Paulo Ferreira (2011)
Having as purpose the development of rhythmic and motor abilities in subjects with little dance experience, we will reflect on questions of pedagogy, namely in what concerns to the use of musical and traditional dances from different cultures in educational music contexts.For a repertoire of music and traditional dances that we have been using with children from kindergarten and primary, as well in the training of kindergarten educators, teachers and sociocultural intervention, we suggest an analysis of choreographic structures according to rhythmic criteria of duration and accentuation, particularly in terms of rhythmic patterns (motifs and phrases). We will refer to various choreographic variables that might have influence into the motor-rhythmic perception andperformance, specifying a progression of space variables.We also suggest a progression of music and movement activities to assess the level of motor-rhythmic performance, presenting indicators for observation. Finally, we present a systematic progression in rhythmic and movement activities andstrategies with a motor-rhythmic focus.